Chief Executive Officer Proactive Personality and Acquisitions: A Fuzzy Set Qualitative Comparative Analysis of China's Listed Firms - Yang, Gang; Bai, Xueyan; Yang, Shiyu (Frontiers in Psychology, 2021)
The role of CEO in an enterprise’s management decisions renders their individual characteristics influential in decisions about mergers and acquisitions (M&As). Personal characteristics are based on many aspects, therefore, we provide a multi-angle insight into the personal characteristics of managers. Drawing on the upper echelons theory, we examine whether CEOs’ proactive personality affects merger and acquisition decisions. The fuzzy-set qualitative comparative analysis (fsQCA) is performed using a sample of 64 listed firms in China for the period 2010–2019. There are three solutions for cross-industry mergers, and five for intra-industry mergers. The results suggest that: (a) proactive and overconfident CEOs are inclined toward cross-industry mergers; (b) non-proactive and low-educated CEOs are inclined toward intra-industry mergers; (c) emerging industry enterprises tend to choose intra-industry mergers; (d) overconfident CEOs are more likely to undertake cross-industry mergers in traditional industries.